B cell abnormalities and autoantibody production in patients with partial RAG deficiency - Min, Qing; Csomos, Krisztian; Li, Yaxuan; Dong, Lulu; Hu, Ziying; Meng, Xin; Yu, Meiping; Walter, Jolan E.; Wang, Ji-Yang (Frontiers in Immunology, 2023)
Mutations in the recombination activating gene 1 (RAG1) and RAG2 in humans are associated with a broad spectrum of clinical phenotypes, from severe combined immunodeficiency to immune dysregulation. Partial (hypomorphic) RAG deficiency (pRD) in particular, frequently leads to hyperinflammation and autoimmunity, with several underlying intrinsic and extrinsic mechanisms causing a break in tolerance centrally and peripherally during T and B cell development. However, the relative contributions of these processes to immune dysregulation remain unclear. In this review, we specifically focus on the recently described tolerance break and B cell abnormalities, as well as consequent molecular and cellular mechanisms of autoantibody production in patients with pRD.